Analisa Transaksi Penjualan Dalam peningkatan Promosi Penjualan Berbasis Sistem Informasi - Maresta Dora; Riki Khairul; Wisdalia Maya Sari (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
all have recorded all sales transactions into the information system, it's just that the existing data is not used as new information for the next marketing strategy. Data Analysis This sales transaction will combine with a computer, namely data mining techniques to find the rules of a combination of items. One of the stages of association analysis that has attracted the attention of many researchers to produce efficient algorithms is high-frequency pattern mining. The output of data mining can be used to improve future decision making. The purpose of using data mining with the Apriori Algorithm is to find out the results of product sales data processing, so that it can make a marketing strategy to place products that are often purchased, making it easier for consumers to find the location of products to save time. Association analysis or association rule mining is a data mining technique to find the rules of a combination of items. One of the stages of association analysis that has attracted the attention of many researchers to produce efficient algorithms is high-frequency pattern mining. Support is the value of support or percentage combination of an item in the database. While confidence is the value of certainty, namely the strength of the relationship between items in an a priori (Srikanti et al. 2018). The purpose of using data mining with the Apriori Algorithm is the result of processing product sales data, so that it can make marketing strategies to place products that are often purchased, making it easier for consumers to find product location to save time (Nugraha et al. 2016). The priority of this research is the creation of an Apriori Algorithm implementation in the sales transaction system at XYZ Supermarkets. in the data processing so that the data stored in the database will become information that can be used to assist in determining the marketing strategy of XYZ Supermarkets in the future.